2021
DOI: 10.1007/s11142-020-09567-4
|View full text |Cite|
|
Sign up to set email alerts
|

Management forecasts of volatility

Abstract: We examine the predictive information content of the management forecasts of stock return volatility (i.e., expected volatility) that are disclosed in annual reports. We find that expected volatility predicts near-term and longer-term stock return volatility and earnings volatility incremental to implied volatility, historical volatility, firm characteristics, and alternative measures of uncertainty. We also find that expected volatility reflects managers’ private information about their firms’ future investme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…This suggests that for firms in weak-institution countries, SOA and financial statement attestation (as proxied by higher audit fees) act as complements, allowing firms to make a more credible commitment to return economic earnings to investors. In column 4, we find a significantly positive coefficient on the interaction of Return Volatility-a measure of information uncertainty (Zhang [2006], Ellahie and Peng [2021]) that we calculate as the standard deviation of daily stock returns over the prior year-and Institutional Quality. This finding suggests information and agency conflicts are less pronounced (i.e., information uncertainty is lower) in weak-as opposed to strong-institution countries when the firm has a high SOA.…”
Section: Firm-level Characteristics and Soamentioning
confidence: 93%
“…This suggests that for firms in weak-institution countries, SOA and financial statement attestation (as proxied by higher audit fees) act as complements, allowing firms to make a more credible commitment to return economic earnings to investors. In column 4, we find a significantly positive coefficient on the interaction of Return Volatility-a measure of information uncertainty (Zhang [2006], Ellahie and Peng [2021]) that we calculate as the standard deviation of daily stock returns over the prior year-and Institutional Quality. This finding suggests information and agency conflicts are less pronounced (i.e., information uncertainty is lower) in weak-as opposed to strong-institution countries when the firm has a high SOA.…”
Section: Firm-level Characteristics and Soamentioning
confidence: 93%
“…One, Generally Accepted Accounting Principles (GAAP), and second, the International Financial Reporting Standard (IFRS). It has been used extensively to examine several matters such as taxation (Folorunso & Lokanan, 2022;Fernando et al, 2021), board characteristics (Khan & Kamal, 2022;Almarayeh et al,2022), stock return (Ellahie & Peng, 2021;Derun & Mysaka, 2021;Al Mamun et al, 2021;Bouaziz et al, 2020), readability (El-Din et al, 2021;Liu & Liu, 2021;Bradley et al,2021;Arora & Chauhan, 2021;Napier & Stadler, 2020), corporate social responsibility (Habbash & Haddad, 2019), and award (Deng et al, 2020) in last four years.…”
Section: Evidence On Earnings Management Activities Simulated Kalman ...mentioning
confidence: 99%
“…For centuries, financial report has been used to forecast stock return (Ellahie & Peng, 2021;Derun & Mysaka, 2021) and firms that have top management counsel (TMC) are less likely to have stock price decline (Al Mamun et al, 2021). Al Mamun et al (2021) found that TMCs are more effective at lowering the risk of collisions when they are the board members as their role is to monitor the reduction of negative news hoarding, which lowers the risk of earnings management.…”
Section: Earnings Management Activities In Stock Returnmentioning
confidence: 99%